2011
DOI: 10.1007/s10661-011-1889-x
|View full text |Cite
|
Sign up to set email alerts
|

Organotin compounds in surface sediments from seaports on the Gulf of Gdańsk (southern Baltic coast)

Abstract: Sediment samples were collected in two Polish ports of international significance-the Port of Gdańsk and the Port of Gdynia (Gulf of Gdańsk, Baltic Sea)-in order to assess their butyltin and phenyltin contamination; this was done in 2008, just after the total ban on using harmful organotins in antifouling paints on ships came into force. Altogether, 21 sampling stations were chosen to present a diversity of port sites: from port canals and shipyards to anchorages and dumping sites. The organic carbon content a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 27 publications
(31 reference statements)
1
25
1
6
Order By: Relevance
“…But the correlations between MBT and TBT, MPhT and TBT were not significant. The results are differed from some literatures [7,14], in which high correlations between MBT and TBT were obtained, and MBT were thought as a degraded product of TBT. However, the data in the present study indicated the possible direct discharge of MBT to coastal environments.…”
Section: Correlations Among the Otcs Speciescontrasting
confidence: 99%
See 1 more Smart Citation
“…But the correlations between MBT and TBT, MPhT and TBT were not significant. The results are differed from some literatures [7,14], in which high correlations between MBT and TBT were obtained, and MBT were thought as a degraded product of TBT. However, the data in the present study indicated the possible direct discharge of MBT to coastal environments.…”
Section: Correlations Among the Otcs Speciescontrasting
confidence: 99%
“…TBT can cause chronic and acute toxic effects to algae, zooplankton, mollusks, and some fish species even at very low concentrations [4−6]. TPhT is less toxic than TBT, but can also be of high risk to aquatic life [1,7].…”
mentioning
confidence: 99%
“…In general, low concentrations of BTs detected in surface sediments may be a result of (i) sampling location, as some samples may be located far from the main sources, (ii) a decrease in input because of the TBT-based antifouling paint ban, and (iii) degradation in the environment caused by hydrodynamic processes and human activities, such as dredging and ship traffic (Radke et al 2008). Whereas in some environments, TBT impact was reduced after the antifouling ban (Airaksien et al 2010;Garg et al 2009), in other areas (mainly development countries), the concentrations detected after the ban were higher (Filipkowska et al 2011;Kim et al 2011;Kim et al 2015). Corresponding with these results, Paranaguá and Itajaí (located along the Brazilian southern coast) were the most impacted estuaries, as the presence of BTs was observed in biotic and abiotic matrices.…”
Section: Integrative Resultsmentioning
confidence: 60%
“…Although TBT in antifouling paints was banned globally by the International Marine Organization in January 2008, TBT can still be found in the aquatic environment (Filipkowska et al 2011;Kim et al 2011;Sant'Anna et al 2014;Santos et al 2010) due to its relative stability in these systems. In estuarine environments, numerous factors, including temperature, salinity, pH, redox potential, organic matter content, and grain size of sediments, can affect the distribution of BTs, and all these factors are related to the speciation, complexation, and bioavailability of BTs for aquatic biota (Hoch 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, data for TBTCl solubility in the water range from 5 to 50 mg L -1 , whereas dibutyltin dichloride (DBTCl 2 ) solubility is higher, up to 92 mg L -1 (Rudel, 2003). Due to its low water solubility, OTs strongly bind to suspended material and inorganic sediments (Laughlin Jr et al, 1986), just as shallow marine sediments (de Oliveira et al, 2010;Filipkowska et al, 2011;Okoro et al, 2011;Zhang et al, 2013). OTs are hydrophobic due to the hydrocarbon substituents.…”
Section: Accepted Manuscriptmentioning
confidence: 99%